Two-year outcome of thymectomy with or without immunosuppressive treatment in nonthymomatous myasthenia gravis and its effect on regulatory T cells - Jakubíková, Michala; Piťha, Jiří; Marečková, Helena; Týblová, Michaela; Nováková, Iveta; Schutzner, Jan (Journal of the neurological sciences, 2015)
BACKGROUND: Myasthenia gravis (MG) is the autoimmune disorder in which the thymus is considered the pathogenic organ. Thymectomy (TE) is a therapeutic option for MG and often ameliorates clinical symptoms. METHODS: We evaluated clinical features and outcomes after TE in patients without thymoma and the influence of TE with or without concomitant immunotherapy on the CD4(+)CD25(+) regulatory T cell subpopulation of lymphocytes in peripheral blood in defined followed groups of nonthymomatous MG patients. RESULTS: A total of 46 patients with generalized MG who underwent transsternal TE were identified. Neurologic outcomes after TE were favorable for the majority of patients mainly from the group treated with corticosteroids or combined immunosuppressive treatment. TEs with immunosuppressive treatment in MG patients were associated with increased percentages of CD4(+)CD25(+) cells (p<0.001). No significant change in the postoperative levels of CD4(+)CD25(+) cells was observed in thymectomized patients who preoperatively only received pyridostigmine. Also their clinical response to TE after 2 years of follow-up was worst of all followed groups. CONCLUSIONS: The exact mechanism by which TE ameliorates symptoms of MG is yet not clear. These observations indicate that increased percentages of CD4(+)CD25(+) T cells in MG may be related to disease stability and that TE and synergistic effect with concomitant, continuing immunotherapy augmented the proportion of CD4(+)CD25(+) T cells. On the basis of our observations TE alone is not enough to increase the number of circulating CD4(+)CD25(+) regulatory T cells and to establish complete stable remission.
Keywords: receptor interleukinu-2 - alfa-podjednotka; kombinovaná terapie; Young Adult; CD4(+) CD25(+) regulatory T-lymphocytes; Male; Combined Modality Therapy; Immunosuppressive Agents; Pyridostigmine; mladý dospělý; Combined immunosuppressive treatment; následné studie; regulační T-lymfocyty; hormony kůry nadledvin; myasthenia gravis; kombinovaná farmakoterapie; Adult; počet lymfocytů; dospělí; mužské pohlaví; Myasthenia gravis; Drug Therapy, Combination; CD4 Lymphocyte Count; Thymectomy; CD4 Antigens; Follow-Up Studies; počet CD4 lymfocytů; antigeny CD4; T-Lymphocytes, Regulatory; Lymphocyte Count; Myasthenia Gravis; hodnocení výsledků zdravotní péče; lidé; ženské pohlaví; Humans; QMG score; Corticosteroids; Adrenal Cortex Hormones; Interleukin-2 Receptor alpha Subunit; Outcome Assessment, Health Care; Female; lidé středního věku; thymektomie; imunosupresiva; Middle Aged